Social Investment Bonds in the European Context - Norbert Wohlfahrt (Social Work and Society, 2019)
Social Impact or Investment Bonds are relatively new forms of financing social services. The coordination of social service production is changed by them in many related dimensions: replacement of government funding of social innovations by capital pre-funding, replacement of non-profit organised provision of services by social enterprises, replacement of legally funded (output-orientated) actions in social services by impact oriented performance and finance. Empirical research shows different types of Social Investment Bonds in European countries, but their common approach is the implementation of impact orientation in the production of social services. There is a strong link between the high importance of impact orientation and the austerity regime in the capitalist states of Europe: the government saves short-term investment and combines this with new challenges concerning impact performance. So called Evidence based social work is becoming part of cost management strategies by the (local) social state and therefore it helps to realize defined political-administrative outcome goals. Social investment bonds are a new type of privatization in social services - and even if they fail they will probably establish a new political economy of social service production.